Analyses of local control and survival after stereotactic body radiotherapy for pulmonary oligometastases from colorectal adenocarcinoma. (17th September 2020) - Yamamoto, Takaya; Niibe, Yuzuru; Matsumoto, Yasuo; Onishi, Hiroshi; Aoki, Masahiko; Nishikawa, Atsushi; Oh, Ryoong-Jin; Shintani, Takashi; Yahara, Katsuya; Ozaki, Masatoki; Manabe, Yoshihiko; Jingu, Keiichi
Abstract: This study is a subset analysis of a retrospective multicenter study performed in Japan and its purpose was to investigate the effectiveness of stereotactic body radiotherapy (SBRT) for pulmonary oligometastases from colorectal cancer. Local control (LC), freedom from further metastases, relapse-free survival and overall survival (OS) after SBRT were retrospectively analyzed. The Kaplan–Meier method was used to estimate lifetime data and the log-rank test was performed as univariate analyses. The Cox proportional hazards model was applied in multivariate analyses. Data for 330 patients with 371 tumors were used for analyses. The median follow-up period was 25.0 months. The 3-year LC, freedom from further metastases, relapse-free survival and OS rates were 64.9, 34.9, 24.9 and 63.4%, respectively. The results of multivariate analyses showed that a higher LC rate was associated with no history of local therapy for oligometastases ( P  = 0.01), SBRT without concurrent chemotherapy ( P  < 0.01), type B calculation algorithm ( P  < 0.01) and higher biological effective radiation doses (≥115 Gy, P  = 0.04). A longer OS was associated with no history of local therapy for oligometastases ( P  = 0.04), a more recent period of SBRT (2010–15, P  = 0.02), tumor located in the upper or middle lobe ( P  < 0.01) and higher biological effective radiation doses (≥115 Gy, P  = 0.01). In conclusion, OS after SBRT was good, but LC rate was relatively low. The use of high biological effective radiation doses can improve both LC and OS outcomes.